Bronchial responsiveness, lung mechanics, gas transfer, and corticosteroid response in patients with chronic airflow obstruction. Issue 11 (November 1988) - James, A L; Finucane, K E; Ryan, G; Musk, A W
Abstract : Thirty patients with stable chronic airflow obstruction receiving regular bronchodilator treatment were studied to determine whether the level of bronchial responsiveness, transfer factor for carbon monoxide (TLCO), or the mechanical properties of the lung predicted a bronchodilator response to oral corticosteroid treatment. Before treatment mean (SD) FEV1 was 48% (16%) of the predicted value (% pred); the geometric mean concentration of methacholine required to produce a 20% fall in FEV1 (PC20) was 0.44 (range 0.07-3.32) mg/ml; and TLCO was 59% (21%) predicted. The exponential constant (k) defining the shape of the static volume-pressure curve was 146% (66%) predicted and pulmonary conductance relative to predicted lung volume at a transpulmonary pressure of 5 cm H2O (sGL5) was 72% (37%) predicted. After prednisolone treatment (0.6 mg kg-1 day-1 for two weeks) FEV1 increased by 8% (19%) (p less than 0.05) and daily mean peak flow (PEF) by 3% (10%) (p less than 0.01) over pretreatment values. Three patients had an increase in FEV1 of more than 30%, two of whom had sputum eosinophilia (p less than 0.05). The three were among the 13 patients with a reduced sGL5. The increase in FEV1 did not correlate with initial PC20 (r = 0.16), k (r = -0.12), or TLCO (r = -0.14). Thus measurements of bronchial responsiveness, lung distensibility, and TLCO did not predict corticosteroid response in patients with stable chronic airflow obstruction. Patients with sputum eosinophilia or reduced pulmonary conductance may be more likely to respond.